IMPLEMENTASI KERJASAMA NATIONAL CENTRAL BUREAU-INTERPOL INDONESIA DENGAN NATIONAL CENTRAL BUREAU-INTERPOL AUSTRALIA DALAM EKSTRADISI TERSANGKA KORUPSI STUDI KASUS: ADRIAN KIKI ARIAWAN - Monica Ihut Maritho (2020)
This study aims to analyze the implementation of the cooperation between National Central Bureau-INTERPOL Indonesia and National Central Bureau-INTERPOL Australia in extradition of corruption suspect Adrian Kiki Ariawan. This study used qualitative research methods that are supported by theories and concepts used to study this research which are bilateral cooperation, transnational crime, and extradition treaty. National Central Bureau-INTERPOL Indonesia is one of the Bureaus in the organizational structure of the International Relations Division of the Indonesian National Police (Divhubinter Polri) which carries the task of implementing international cooperation, bilateral and multilateral cooperation with the aim to combating international or transnational crime. One of the transnational crime cases handled by the National Central Bureau-INTERPOL Indonesia is Adrian Kiki Ariawan's corruption case. Adrian Kiki Ariawan was a President Director of PT. Bank Surya Tbk who got entangled in a corruption case of Bank Indonesia Liquidity Assistance and fled to Australia so that cooperation was needed between the National Central Bureau-INTERPOL Indonesia and the National Central Bureau-INTERPOL Australia to extradite Adrian from Australia to Indonesia. The cooperation worked effectively despite the challenge and obstacle they encountered in the extradition process of Adrian Kiki Ariawan.